Emerging two-dimensional silicene nanosheets for biomedical applications. (December 2021) - You, Y.; Yang, C.; Zhang, X.; Lin, H.; Shi, J.
Abstract: Advanced and tremendous research in two-dimensional (2D) materials have unlocked valuable capabilities that lead to a new materials era. Silicene, as a rising-star 2D material, that features multifaceted properties, such as high specific surface area, excellent optical properties, unique electronic properties, and desirable biocompatibility and biodegradability, provides a promising opportunity for applications in different fields expanding from electronic science to biomedicine. The interesting outcomes obtained so far and the evident progress have highlighted the extraordinary potential of silicene in biomedical applications, including tumor therapeutics, bioimaging, and antimicrobial materials. In this review, we comprehensively present the up-to-date developments of silicene in the biomedical field. We discuss silicene-based nanodrugs starting from silicene synthetic strategies to the rational design of multifunctional nanomedicine. We also emphasize the biosafety evaluation to promote the translation of silicene materials into innovative clinical tools. Finally, we sum up new trends and present suggestions for future developments of silicene-based nanomedicine. Graphical abstract: An overview of the properties and applications of silicene-based nanomaterials in biomedical science. Image 1